2014
DOI: 10.1182/blood-2013-07-517136
|View full text |Cite|
|
Sign up to set email alerts
|

Osteoblastic niche supports the growth of quiescent multiple myeloma cells

Abstract: • Osteoblastic niche supports quiescent multiple myeloma cells in vivo.• Multiple myeloma cells isolated from osteoblastic niche have enhanced tumorigenicity and stemlike properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 8 publications
(4 reference statements)
4
73
0
1
Order By: Relevance
“…Whereas the presence of Wnt ligands in the BM niche is well established, expression of R-spondins in the BM microenvironment thus far has remained largely unexplored. Because autocrine R-spondins have been suggested to regulate differentiation of osteoblasts (38), which are important constituents of the MM niche (39,40), we hypothesized that osteoblasts could be a major source of R-spondins driving oncogenic Wnt signaling. Corroborating this hypothesis, we found expression of several R-spondins in (pre)osteoblasts and demonstrated that (pre)osteoblast-conditioned media robustly synergized with Wnt ligands in activating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the presence of Wnt ligands in the BM niche is well established, expression of R-spondins in the BM microenvironment thus far has remained largely unexplored. Because autocrine R-spondins have been suggested to regulate differentiation of osteoblasts (38), which are important constituents of the MM niche (39,40), we hypothesized that osteoblasts could be a major source of R-spondins driving oncogenic Wnt signaling. Corroborating this hypothesis, we found expression of several R-spondins in (pre)osteoblasts and demonstrated that (pre)osteoblast-conditioned media robustly synergized with Wnt ligands in activating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the source of R-spondins remains to be defined. Prime candidates are osteoblasts, which have recently been suggested to use autocrine R-spondin for their differentiation (38) and, moreover, are key constituents of the MM niche (39,40). We therefore analyzed R-spondin mRNA expression in primary human osteoblasts (hOB) by qPCR.…”
Section: R-spondins Potentiate Wnt Signaling In MM In a Lgr4-dependentmentioning
confidence: 99%
“…9 The potential quiescence of these MM subclones, coupled with their diversity, can contribute to enhanced tumorigenicity and an intrinsic resistance to therapy. 10 Therefore; the eradication of the majority bortezomib-sensitive subclones may ultimately promote the growth of pre-existing minority bortezomib-resistant sub-clones, limiting the efficacy of single-agent bortezomib. This finding is further supported by the clinical observation that approximately half of initially bortezomib-sensitive MM patients are no longer able to respond to bortezomib once relapsed.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the role of angiogenesis in diffuse large B cell lymphoma measured by microvessel density has shown different results in regard to clinical outcome [32,33]. MM cells grow and expand almost exclusively in the bone marrow [34], and both osteoblastic and vascular niches can support the proliferation of MM cells [35]. This emphasizes Figure 2.…”
Section: Discussionmentioning
confidence: 97%